Bio-physical evaluation and in vivo delivery of plant proteinase inhibitor immobilized on silica nanospheres - Khandelwal, Neha; Doke, Dhananjay S.; Khandare, Jayant J.; Jawale, Priyanka V.; Biradar, Ankush V.; Giri, Ashok P. (Colloids and Surfaces B-Biointerfaces, 2015)
Recombinant expression of Capsicum annuum proteinase inhibitors (CanPI-13) and its application via synthetic carrier for the crop protection is the prime objective of our study. Herein, we explored proteinase inhibitor peptide immobilization on silica based nanospheres and rods followed by its pH mediated release in vitro and in vivo. Initial studies suggested silica nanospheres to be a suitable candidate for peptide immobilization. Furthermore, the interactions were characterized biophysically to ascertain their conformational stability and biological activity. Interestingly, bioactive peptide loading at acidic pH on nanospheres was found to be 62% and showed 56% of peptide release at pH 10, simulating gut milieu of the target pest Helicoverpa armigera. Additionally, in vivo study demonstrated significant reduction in insect body mass (158 mg) as compared to the control insects (265 mg) on 8th day after feeding with CanPI-13 based silica nanospheres. The study confirms that peptide immobilized silica nanosphere is capable of affecting overall growth and development of the feeding insects, which is known to hamper fecundity and fertility of the insects. Our study illustrates the utility and development of peptide-nanocarrier based platform in delivering diverse biologically active complexes specific to gut pH of H. armigera. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biodelivery; Helicovera armigera; Protein `corona'; Proteinase inhibitor; Silica nanospheres

Calcium phosphate nanocapsule crowned multiwalled carbon nanotubes for pH triggered intracellular anticancer drug release - Banerjee, Shashwat S.; Todkar, Kiran J.; Khutale, Ganesh V.; Chate, Govind P.; Biradar, Ankush V.; Gawande, Manoj B.; Zboril, Radek; Khandare, Jayant J. (Journal of Materials Chemistry B, 2015)
We report calcium phosphate (CaP) nanocapsule crowned multi-walled carbon nanotubes (CNT-GSH-G4-CaP) as a novel platform for intracellular delivery of an anticancer drug. As a proof-of-concept, CNT-GSH-G4-CaP demonstrates release of anticancer drug doxorubicin hydrochloride (DOX) within intracellular lysosomes from the interior cavity of CNT upon pH triggered CaP dissolution. Importantly, we found that the CNT with a CaP nanolid can efficiently prevent untimely drug release at physiological pH but promotes DOX release at increased acidic milieu as observed in subcellular compartments such as lysosomes (similar to 5.0). This ``zero premature release'' characteristic is of clinical significance in delivering cytotoxic drugs, by reducing systemic toxicity and thus beneficial for the effective anticancer treatment. We envision that this pH triggered CaP crowned CNT nanosystem would lead to a new generation of self-regulated platforms for intracellular delivery of a variety of anticancer drugs.

Budding trends in integrated pest management using advanced micro- and nano-materials: challenges and perspectives - Khandelwal, Neha; Barbole, Ranjit S.; Banerjee, Shashwat S.; Chate, Govind P.; Biradar, Ankush V.; Khandare, Jayant J.; Giri, Ashok P. (Journal of Environmental Management, 2016)
One of the most vital supports to sustain human life on the planet earth is the agriculture system that has been constantly challenged in terms of yield. Crop losses due to insect pest attack even after excessive use of chemical pesticides, are major concerns for humanity and environment protection. By the virtue of unique properties possessed by micro and nano-structures, their implementation in Agri-biotechnology is largely anticipated. Hence, traditional pest management strategies are now forestalling the potential of micro and nanotechnology as an effective and viable approach to alleviate problems pertaining to pest control. These technological innovations hold promise to contribute enhanced productivity by providing novel agrochemical agents and delivery systems. Application of these systems engages to achieve: i) control release of agrochemicals, ii) site-targeted delivery of active ingredients to manage specific pests, iii) reduced pesticide use, iv) detection of chemical residues, v) pesticide degradation, vi) nucleic acid delivery and vii) to mitigate post-harvest damage. Applications of micro and nano-technology are still marginal owing to the perception of low economic returns, stringent regulatory issues involving safety assessment and public awareness over their uses. In this review, we highlight the potential application of micro and nano-materials with a major focus on effective pest management strategies including safe handling of pesticides. (C) 2016 Elsevier Ltd. All rights reserved.

Designing multicomponent nanosystems for rapid detection of circulating tumor cells - Banerjee, Shashwat S.; Khobragade, Vrushali; Khandare, Jayant J. (Methods in Molecular Biology, 2017)
Detection of circulating tumor cells (CTCs) in the blood circulation holds immense promise as it predicts the overall probability of patient survival. Therefore, CTC-based technologies are gaining prominence as a “liquid biopsy” for cancer diagnostics and prognostics. Here, we describe the design and synthesis of two distinct multicomponent magnetic nanosystems for rapid capture and detection of CTCs. The multifunctional Magneto-Dendrimeric Nano System (MDNS) composed of an anchoring dendrimer that is conjugated to multiple agents such as near infrared (NIR) fluorescent cyanine 5 NHS (Cy5), glutathione (GSH), transferrin (Tf), and iron oxide (Fe3O4) magnetic nanoparticle (MNP) for simultaneous tumor cell-specific affinity, multimodal high resolution confocal imaging, and cell isolation. The second nanosystem is a self-propelled microrocket that is composed of carbon nanotube (CNT), chemically conjugated with targeting ligand such as transferrin on the outer surface and Fe3O4 nanoparticles in the inner surface. The multicomponent nanosystems described here are highly efficient in targeting and isolating cancer cells thus benefiting early diagnosis and therapy of cancer.